Commercial Court and Enforcement Assessment Tool - Ebeid, Omniah; Gramckow, Heike (World Bank, Washington, DC, 2016)
An effective and efficient justice system is essential for sustained economic growth. In a well-functioning, independent, and efficient justice system, decisions are taken within a reasonable time and are predictably and effectively enforced, and individual rights, including property rights, are adequately protected. Among other objectives, the efficiency of the judicial system is important for creating a good business climate, attracting foreign direct investment, securing tax revenues, and supporting economic growth. Research has shown that weak contract enforcement, for example, raises the cost of borrowing and shortens loan maturities, with a resulting negative effect on investment and GDP. Weak court enforcement systems have also been linked to late payments, which can lead to liquidity issues for companies and increase insolvency. Since the publication of the World Bank’s World Development Report 2005, the importance of well-functioning courts to strengthening the investment climate and ultimately to reducing poverty and boosting shared prosperity has been brought to the forefront and become internationally recognized. Indicators of commercial court performance, and business community perceptions of and trust in the courts, are a part of the World Bank Group’s (WBG) country-level investment climate assessments and its influential Investment Climate Surveys and Doing Business reports. Court performance has also become an element of European Union (EU) and Organization for Economic Co-operation and Development (OECD) accession. Helping countries to improve commercial court operations and ensure improved accessibility and effective delivery of services are important components of the development assistance provided by the WBG. The Commercial Court and Enforcement Assessment Tool has been designed to assist assessment teams and client agencies in this effort.